Selective antimicrobial performance of biosynthesized silver nanoparticles by horsetail extract against E. coli - Miljković, M. (2020)
The aim of this study was the development of a non-toxic, biosynthetic antimicrobial agent which selectively acts on only one type of microorganism, and preserves the microbiota. Antimicrobial performance of biosynthesized silver nanoparticles (Ag NPs) by horsetail (Equisetum arvense L.) extract was examined against Gram-negative bacteria Escherichia coli and Gram-positive bacteria Staphylococcus aureus, as well as yeasts Candida albicans and Saccharomyces boulardii. Also, the cytotoxicity of Ag NPs was examined toward pre-osteoblast cells. The synthetic conditions—concentration of extract, temperature, and pH—were optimized to prepare silver colloids with different particle size distributions and long-term stability. The obtained samples were characterized using transmission electron microscopy, X-ray diffraction analysis, and absorption spectroscopy. The smaller-sized Ag NPs (~ 10–20 nm), prepared at a lower temperature (20 °C), showed better antimicrobial performance against E. coli compared to larger ones (~ 40–60 nm), prepared at high temperature (100 °C). On the other hand, both samples did not display any toxic action against bacteria S. aureus, or yeasts C. albicans and S. boulardii. Non-cytotoxic behavior of Ag NPs toward pre-osteoblast cells was observed for the concentrations of silver ≤ 2.25 and ≤ 4.5 mg L−1 for 10–20 and 40–60 nm-sized Ag NPs, respectively. Biosynthesized Ag NPs by horsetail extract display selective toxic action against E. coli at the ecologically acceptable concentration level.